2013
DOI: 10.6018/ijes/2013/1/152681
|View full text |Cite
|
Sign up to set email alerts
|

A study of the acquisition of discourse markers by Chinese learners of English

Abstract: This study investigates the acquisition of discourse markers by Chinese learners of English in terms of gender, style and individual identity. The subjects of the study are 15 female university students and 15 male university students. The data is collected by means of audio recording in the classroom discussion and in the interviews. The examined discourse markers are like, yeah, oh, you know, well, I mean, right, ok and actually , and a total of 1292 tokens for these discourse markers are identified in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
(22 reference statements)
1
6
0
1
Order By: Relevance
“…A similar distributional pattern between NNS and NS speech has been observed in the functional category of you know marking common ground information. This function of you know has been reported in previous research as well (Bu, 2013;House, 2009;Huang, 2011;Müller, 2005). An example of this assumed common ground is seen in ( 5) and ( 6).…”
Section: Functional Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…A similar distributional pattern between NNS and NS speech has been observed in the functional category of you know marking common ground information. This function of you know has been reported in previous research as well (Bu, 2013;House, 2009;Huang, 2011;Müller, 2005). An example of this assumed common ground is seen in ( 5) and ( 6).…”
Section: Functional Analysissupporting
confidence: 78%
“…Depending on the fact that studying discourse markers is at the interjection of syntax, pragmatics and semantics, it is admittedly a difficult task to create definitive lists of DMs in a language, -even little agreement has been reached on its terminology. Various researchers examined the concept under various labels such as "discourse particles" (Aijmer & Stenström, 2002), "pragmatic markers" (Aijmer, 2004;Downing, 2006;Wei, 2011), "discourse connectives" (Blakemore, 1992), among them "discourse markers" (Bu, 2013;Buysse, 2012;Fraser, 2006;Gilquin, 2016;Müller, 2005;Polat, 2011;Romero-Trillo, 2002) being the most widely used term in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The ELLs in Iglesias Moreno's (2001) study did not make much use of discursive well and when they did, the uses were often deemed "inappropriate." Bu (2013) also discovered that only one out of the 30 ELLs in that study used the DM and only twice. On the contrary, Müller (2004) found that ELLs had a higher frequency rate for well than EDSs.…”
Section: Comparison To Others' Findingsmentioning
confidence: 89%
“…The findings have indicated that ELLs have a different rate of frequency, greater variation among the learner group, and a limited range of functions in DM use in comparison to EDSs. Bu (2013) examined the acquisition of DMs such as like and well, among others, by Chinese ELLs, and concluded that there was variation in frequency, gender, and style among the ELLs, and that their use of the DMs' functions was limited compared to that of native speakers. Similarly, Liao (2008) inferred that the learners in that study had only obtained partial acquisition of the DMs' functions and that context was a good indicator of which DM would be used in the talk.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the acquisition of PMs, research analyzing the effects of ISLA shows that learners tend to use PMs for a much narrower scope and frequency than NSs do, as they seem to struggle to correctly identify the functions of the items. For example, Bu (2013) found that while learners used the same PMs as NSs, they did not use them for the same functions as the NSs did, resulting in both a restricted range and an unnatural use of PMs. Müller (2005) reported similar findings; she found that in addition to differing patterns of PM use, learners also assigned new functions to PMs not found in the native discourse.…”
Section: The Acquisition Of Pragmatic Markers In Instructed Second Language Acquisitionmentioning
confidence: 99%